The Euro Area: Conventional Theory and a Digital Future - Todorov, Ivan (Research Papers, 2024)
The development of technology predetermines the execution of numerous operations with the help of private digital currencies, which, however, avoid the necessary supervision. If the adoption of these non-traditional payment methods significantly expands, private digital currencies could potentially undermine the authority of central banks to provide liquidity to the economy. The response of the central banks has been consistent and at the moment discussions on the introduction of digital currency issued by the central bank is on the agenda. The study reports progress in this direction by presenting the features of the modern financial system in the Eurozone, as well as the place, role and transformative power of the digital euro in it.